Extreme rainfall analysis of Andhra Pradesh using a probability distribution model : A regional estimate - GUHATHAKURTA, P.; MENON, P. A.; DIKSHIT, S. K.; SABLE, S. T. (MAUSAM, 2005)
The study is an attempt to analyze the extreme rainfall events of Andhra Pradesh, a coastal state of Peninsular India, where both monsoon and post-monsoon seasons contribute significant rain. A network of 155 stations having data of seventy years or more during the period 1901-2000 has been used for the study. These stations are well distributed over the state. One-day, two-day and three-day extreme annual rainfall series are made and the isohyetal analysis demarcates three heavy rainfall receiving zones. Probability distribution functions have been fitted for the regional estimates of climate changes in extreme rainfall series of each station. Both the extreme value distribution viz., Gumbel and log normal distribution fit well with latter one giving slightly better fit over the former. Goodness of fit of the distribution is tested with Kolmogorov - Smirnov Statistic.